Skills and education for growth and well-being in Europe 2020: are we on the right path? - Theodoropoulou, Sotiria (Brussels, 2010)
"Last June European leaders agreed the Europe 2020 strategy to aim for smart, sustainable and inclusive growth, and introduced a headline target on education and skills. This issue paper by EPC Policy Analyst Sotiria Theodoropoulou evaluates whether these education targets can help achieve these growth goals, given the constraints in public finances. Among its recommendations are to: prioritise public investment in high-quality, early education, develop indicators to measure skills and the quality of education systems, invest in job creation, and for the EU to monitor education goals in coordination with other key policy areas of its competence."